2021
DOI: 10.1039/d1ra01890f
|View full text |Cite
|
Sign up to set email alerts
|

A visible light active, carbon–nitrogen–sulfur co-doped TiO2/g-C3N4 Z-scheme heterojunction as an effective photocatalyst to remove dye pollutants

Abstract: The CNS-TiO2/g-C3N4 photocatalyst with excellent visible light catalytic activity was successfully manufactured, benefiting from the construction of the Z-scheme heterojunction and the co-doping of heteroatoms (C, N and S).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…Potassium iodide (KI) was used as a hole scavenging agent, silver nitrate (AgNO 3 ) as an electron scavenging agent, isopropanol and ascorbic acid were used as OH˙ and O 2 − ˙ radical scavenging agents, respectively. 82 From the graph shown in Fig. S15 (ESI†), it was found that the efficacy in the presence of holes and electron scavengers remained almost the same, while it got retarded in the presence of radical scavengers.…”
Section: Mechanistic Study Of Dye Degradationmentioning
confidence: 97%
See 2 more Smart Citations
“…Potassium iodide (KI) was used as a hole scavenging agent, silver nitrate (AgNO 3 ) as an electron scavenging agent, isopropanol and ascorbic acid were used as OH˙ and O 2 − ˙ radical scavenging agents, respectively. 82 From the graph shown in Fig. S15 (ESI†), it was found that the efficacy in the presence of holes and electron scavengers remained almost the same, while it got retarded in the presence of radical scavengers.…”
Section: Mechanistic Study Of Dye Degradationmentioning
confidence: 97%
“…This implied that CoO x –S–VO x can serve as a better photocatalyst in MO dye degradation by relaxing the electron–hole recombination rate. 82…”
Section: Mechanistic Study Of Dye Degradationmentioning
confidence: 99%
See 1 more Smart Citation
“…The following supporting information can be downloaded at: https:// www.mdpi.com/article/10.3390/nano14010103/s1, Figure S1 S1: Normalized reaction rate (k) values for the MO photodegradation reaction in the presence of photocatalytic samples exfoliated at 550 • C and 600 • C; Table S2: Performance of C 3 N 4 -based samples for degradation of MO under visible light irradiation in recently published literature. References [131][132][133][134][135][136][137][138][139][140][141] are cited in the Supplementary Materials.…”
Section: Supplementary Materialsmentioning
confidence: 99%
“…The following supporting information can be downloaded at: , Figure S1: TEM images of thermally exfoliated g-C 3 N 4 samples: (a and b) 550-CN and (c and d) 600-CN; Figure S2: g-C 3 N 4 sample ultrasonicated in acid media for 40 min; Figure S3: Enlarged view of (002) peak of XRD for g-C 3 N 4 samples; Figure S4: DRS spectra of g-C 3 N 4 samples prepared under different conditions; Figure S5: Pore size distribution curves of different g-C 3 N 4 samples; Figure S6: Visible light degradation spectra of MO using samples (a) 500-CN, (b) 500-UCN, (c) 550-CN, (d) 550-UCN, (e) 550-AUCN, (f) 600-CN, (g) 600-UCN, and (h) 600-AUCN; Figure S7: Photocatalytic degradation of MO under visible light using photocatalyst samples exfoliated at 550 °C; Figure S8: Photocatalytic degradation of MO under visible light, using photocatalyst samples exfoliated at 600 °C; Figure S9: Photocatalytic stability of 500-AUCN in four successive cycling reactions under visible light irradiation; Table S1: Normalized reaction rate ( k ) values for the MO photodegradation reaction in the presence of photocatalytic samples exfoliated at 550 °C and 600 °C; Table S2: Performance of C 3 N 4 -based samples for degradation of MO under visible light irradiation in recently published literature. References [ 131 , 132 , 133 , 134 , 135 , 136 , 137 , 138 , 139 , 140 , 141 ] are cited in the Supplementary Materials.…”
mentioning
confidence: 99%